Clinical Implications of Carcinoma In Situ in Sinonasal Inverted Papilloma - Maina, Ivy W; Tong, Charles C L; Baranov, Esther; Patel, Neil N; Triantafillou, Vasiliki; Kuan, Edward C; Kohanski, Michael A; Papagiannopoulos, Peter; Yan, Carol H; Workman, Alan D; Lambert, Justina L; Cohen, Noam A; et al. (Otolaryngology-head and neck surgery, 2019)
Sinonasal inverted papilloma (IP) is a typically benign sinonasal tumor with a tendency to recur and the potential for malignant transformation. Varying degrees of dysplasia may be present, of which carcinoma in situ (CIS) is most advanced. We hereby describe the biological and clinical behavior of IP with CIS (IPwCIS). Retrospective cohort. Tertiary academic referral center. Patients who underwent surgical resection for IP between 2002 and 2017. Pertinent clinical data were obtained, and all IPwCIS cases were histologically confirmed. In total, 37 of 215 cases (17.2%) were identified with IPwCIS. Mean age was 57 years and 86.5% of patients were male. Median follow-up was 82 months, and the recurrence rate was 27%. The maxillary sinus was the most common primary site (37.8%) and 14 tumors (37.8%) demonstrated multifocal attachment, which was associated with recurrence (odds ratio [OR], 9.7; 95% confidence interval [CI], 1.4-112.8; = .028). IPwCIS was also associated with multiple recurrences (OR, 2.71; 95% CI, 1.246-5.814; = .021). Most patients were treated with surgery alone (89.1%) and 4 patients received adjuvant radiotherapy (8.1%). Only 1 patient (2.7%) demonstrated malignant transformation after definitive surgery. IPwCIS represents the most severe degree of dysplasia prior to malignant transformation and is associated with higher recurrence rate and multifocal involvement but low rate of conversion to invasive carcinoma. The need for adjuvant therapy remains controversial, and further research into the etiology of the disease is warranted.